The analysis of the effectiveness of the seismic noise attenuation by means of Karhunen-Loeve (K-L) transform - KASINA, Zbigniew (Geology, Geophysics and Environment, 2010)
In the paper the analysis of the effectiveness of multiples and random noise attenuation using Karhunen-Loeve (K-L) transform is presented. The K-L transform is realized with application the process Eigenimage Filter in seismic data processing system ProMAX. The basic part of the paper is directed to the analysis of multiples attenuation by means of the K-L transform applied to field data. In the analysis the common shot point gathers (seismic records) were used as well as the traces of the CDP gathers. In the case of CDP gathers the main attention was paid on the multiple attenuation in the averaged CDP gathers (supergathers) prepared for the interactive velocity analysis. The influence of the K-L filter parameters was defined on the effectiveness of multiples removing from the velocity analysis wave images. Finally the effectiveness of the K-L filter was estimated in improving the coherent to random signals ratio on the seismic records.